Querelle, de Genet, de Fassbinder : adaptação e circulação - Carvalho, Gilson Magalhães de (2006)
In this dissertation, we discuss the relations between cinema and literature, through the analysis of the movie Querelle, by German director Rainer Werner Fassbinder, based on the novel Querelle de Brest, by French writer Jean Genet. Issues like fidelity and authorship are examined from the aesthetic choices of the adapter, compatible with the theoretical postulates of Camp and of Neobaroque.